Improved electrode structure

By using low-toxic and environmentally friendly solvents to prepare an improved electrode structure, the cost and hazardous problems of NMP in lithium battery electrodes are solved, and the stability and long-term efficiency of the battery are improved.

CN119542420APending Publication Date: 2025-02-28TAIWAN MAXWAVE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311113451.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium battery pole slurry solvent NMP is expensive, with a risk of reproductive toxicity, which can easily cause environmental and human body harm, and can easily absorb water, resulting in unstability of the battery.

Method used

An environmentally friendly solvent with low toxicity, low odor and low boiling point, such as dimethylformamide (DMF), diethylformamide (DEF), etc., is used to prepare an improved electrode structure, combined with baking treatment to improve battery performance.

Benefits of technology

It reduces the energy consumption during battery manufacturing, solves the environmental and human hazards of NMP, and improves the stability and long-term effectiveness of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542420A_ABST
    Figure CN119542420A_ABST
Patent Text Reader

Abstract

The invention relates to an improved electrode structure, which mainly comprises the following components in percentage by weight: 80-96% of electrode material; a conductive material, wherein the weight percentage of the conductive material is 2-10%; an adhesive agent, wherein the weight percentage of the adhesive agent is 2-10%; the weight percentage of the low-toxicity environment-friendly solvent is 20 to 70 percent of the positive electrode material and 100 to 150 percent of the negative electrode material; wherein the baking temperature of the structure of the improved electrode is 50-150 DEG C, and the processing time is 8-12 hours. According to experiments, the capacitance retention rate of the current commercial non-environment-friendly solvent NMP (N-methyl-2-pyrrolidone) is reduced to 52.1% after 100 times of charging and discharging, while the capacitance retention rate of a sample prepared by using the low-toxicity and low-boiling-point environment-friendly solvent is still 82.5% after 100 times of charging and discharging, and the capacitance retention rate of the sample prepared by using the low-toxicity and low-boiling-point environment-friendly solvent is reduced to 52.1% after 100 times of charging and discharging. Therefore, the low-toxicity environment-friendly solvent has the characteristic of extremely low water absorption and does not generate free amine, so that the pole piece is not easy to deteriorate, and the problem of instability of long-time charging and discharging of the battery is really and effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, in particular to an improved electrode structure. Background Art

[0002] At present, 90% of positive electrode adhesives use oily adhesive PVDF (polyvinylidene fluoride), and PVDF supporting solvent NMP (N-methylpyrrolidone) has reproductive toxicity risks. The EU has proposed relevant policies to restrict the use of NMP; at the same time, due to supply and demand shortages, NMP prices have been rising since the second half of 2021. In addition, NMP thermal decomposition will produce irritating or toxic gases, which are harmful to the environment and human body, so the recycling process must have an additional solvent recovery system. In view of this, the cost of using it in batteries has risen a lot, so material companies and battery companies are actively developing cheaper, more environmentally friendly, and equally excellent lithium battery positive electrode slurry solvents to replace NMP. Therefore, more and more people are moving towards green environmental protection to improve the production process of lithium batteries. However, when water-based adhesives are used in ternary materials, they are easy to produce alkaline compounds with ternary metals, resulting in corrosion effects on aluminum electrodes and affecting battery capacity performance. There is still no better solution. Therefore, according to the direction of solvent development, it can be roughly divided into solvents that do not contain sulfur functional groups, or solvents with cyclic structures are converted into open-ring structures. With the changes in chemical safety regulations, timely selection of low-toxic and environmentally friendly solvents to improve the safety of lithium batteries while also ensuring good battery performance is the focus of the present invention and also the most difficult part.

[0003] In view of the fact that the above-mentioned problems of the prior art cannot be effectively solved and overcome, the inventor of this case, relying on his many years of practical experience and long-term in-depth research on the use of different chemical solvents to prepare lithium battery electrodes, proposed the present invention application to solve the above-mentioned problems. Summary of the invention

[0004] To solve the above problems, a low-toxic, low-odor and low-boiling-point solvent is needed and the solvent is used to prepare the structure of lithium battery electrodes. Low-toxic and environmentally friendly solvents are highly safe for the human body and the environment, and can be both environmentally friendly and maintain the long-term performance of lithium-ion batteries. In detail, it is an improved electrode structure.

[0005] The purpose of the present invention is to provide an improved electrode structure, aiming to utilize a low-toxic and environmentally friendly solvent and use the solvent to prepare a lithium battery pole piece structure, thereby solving the technical problems of the prior art lithium battery pole piece slurry solvent (NMP) being expensive and easily causing harm to the environment and human body, and the solvent being easy to absorb water and easily causing battery instability due to free amines produced during manufacturing or recycling.

[0006] Specifically, the technology used in the present invention is: an electrode material, which includes lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), lithium nickel cobalt aluminum oxide (NCA), silicon oxide carbon composite material (SiOx / C), silicon carbon composite material (Si / C), mesophase carbon microspheres (MCMB), lithium titanate (LTO), wherein the weight percentage of the electrode material is 80-96%; a conductive material, which includes conductive carbon black (Super-P), Ketjen black conductive agent (KB), conductive carbon tube (CNT), graphene (Graphene hene), wherein the weight percentage of the conductive material is 2-10%; an adhesive, the adhesive includes polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyimide (Polyimide), polyethylene oxide (PEO), wherein the weight percentage of the adhesive is 2-10%; and a low-toxicity environmentally friendly solvent, the low-toxicity environmentally friendly solvent includes dimethylformamide (DMF), diethylformamide (DEF), dimethylacetamide (DMAC), tetrahydrofuran (THF), and the chemical formula of the low-toxicity environmentally friendly solvent is (NR2R3OR1) wherein R1=H, Me(-CH3), R2=H, Me(-CH3), Et(-CH2CH3), R3=H, Me(-CH3), Et(-CH2CH3), wherein the weight percentage of the low-toxicity and environmentally friendly solvent in the positive electrode material is 20-70%, and in the negative electrode material is 100-150%; wherein the structure of the improved electrode is given a baking temperature of 50-150 degrees, and the process time is 8 to 12 hours.

[0007] Technical means for solving the problem. In order to achieve the above-mentioned purpose, the present invention provides an improved electrode structure, which mainly includes: an electrode material, the weight percentage of the electrode material is 80-96%; a conductive material, the weight percentage of the conductive material is 2-10%; an adhesive, the weight percentage of the adhesive is 2-10%; and a low-toxicity environmentally friendly solvent, the weight percentage of the low-toxicity environmentally friendly solvent in the positive electrode material is 20-70%, and in the negative electrode material is 100-150%; wherein the baking temperature of the improved electrode structure is 50-150 degrees, and the process time is 8 to 12 hours.

[0008] In an embodiment of the present invention, the electrode material includes lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), lithium nickel cobalt aluminum oxide (NCA), silicon oxide carbon composite material (SiOx / C), silicon carbon composite material (Si / C), mesophase carbon microbeads (MCMB), and lithium titanate (LTO).

[0009] In an embodiment of the present invention, the conductive material includes conductive carbon black (Super-P), Ketjen black conductive agent (KB), conductive carbon tube (CNT), and graphene.

[0010] In an embodiment of the present invention, the adhesive includes polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyimide, and polyethylene oxide (PEO).

[0011] In an embodiment of the present invention, the low-toxicity environmentally friendly solvent includes dimethylformamide (DMF), diethylformamide (DEF), dimethylacetamide (DMAC), and tetrahydrofuran (THF).

[0012] In an embodiment of the present invention, the chemical formula of the low-toxicity environmentally friendly solvent is (NR2R3OR1) where R1=H,Me(-CH3), R2=H,Me(-CH3),Et(-CH2CH3), R3=H,Me(-CH3),Et(-CH2CH3).

[0013] In an embodiment of the present invention, the boiling point of the low-toxicity and environmentally friendly solvent is ≦180° C. at 1 atmosphere.

[0014] In an embodiment of the present invention, the flash point of the low-toxic and environmentally friendly solvent is ≧60° C. and ≦80° C. at 1 atmosphere.

[0015] In an embodiment of the present invention, the thickness of the electrode material is between 50 μm and 200 μm.

[0016] In an embodiment of the present invention, the stirring temperature of the adhesive solution is ≤ 60° C., and the process time is 0.5 to 6 hours.

[0017] Through the above description, the present invention can obtain the following advantages: 1. Replace the existing solvent usage in the battery market.

[0018] 2. Save energy during drying during battery manufacturing - the recycling process requires energy consumption.

[0019] 3. The technical problem that the prior art lithium battery pole piece slurry solvent (NMP) is expensive and easily causes harm to the environment and human body is solved.

[0020] 4. The problem of the solvent easily absorbing water and easily generating free amines during manufacturing or recycling, which causes battery instability, is solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The test results of the battery stability of the electrodes prepared by different solvents of the present invention are as follows; Figure 2 It is the chemical formula of the low-toxicity and environmentally friendly solvent N,N-diethylformamide of the present invention; Figure 3 It is a schematic structural diagram of the improved electrode of the present invention.

[0022] In the figure: 100: Structure of the improved electrode; 10: Electrode material; 20: Conductive material; 30: Adhesive; 40: Low-toxicity and environmentally friendly solvent. Specific implementation manners

[0023] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, so that those skilled in the art can better understand the present invention and be able to implement it, but the examples given are not used to limit the scope of patent application of the present invention.

[0024] Figure 1 It is the test result of the battery stability of the electrodes prepared with different solvents of the present invention, Figure 2 It is the chemical formula of the low-toxicity and environmentally friendly solvent N,N-diethylformamide of the present invention, Figure 3 It is a schematic structural diagram of the improved electrode of the present invention.

[0025] The following embodiments are only preferred examples in the present invention case, so they should not be used to limit the scope of patent application of the present invention case. This embodiment is used to illustrate the preparation of the lithium-ion secondary battery provided by the present invention.

[0026] Example 1 Preparation of the positive electrode 3.2 grams of the positive electrode active ingredient NMC (L x Ni y Mn z Co 1-y-z O2 (0 < x, y, z < 1)), 0.4 grams of the adhesive polyvinylidene fluoride, and 0.4 grams of the conductive agent conductive carbon black are added to 9.6 grams of dimethylacetamide, and then stirred in a ball mill blender to form a uniform positive electrode paste. The paste is uniformly coated on an aluminum foil with a thickness of 20 microns, dried at 120 °C, and cut to obtain a positive electrode plate with dimensions of 120 × 60.0 × 0.08 mm. Then the plate is calendered. Before calendering, the gap X between the two rollers is adjusted so that X = 0.064 mm. After calendering, a positive electrode plate with a thickness of 0.061 mm is obtained. It contains 6.64 mg of the active ingredient NMC.

[0027] Example 2 3.2 g of positive electrode active ingredient LFP (LiFePO4), 0.4 g of adhesive polyvinylidene fluoride, and 0.4 g of conductive carbon black were added to 9.6 g of dimethylacetamide, and then stirred in a ball mill to form a uniform positive electrode slurry. The slurry was evenly coated on an aluminum foil with a thickness of 20 μm, dried at 120°C, and cut to obtain a positive electrode sheet with a size of 120×60.0×0.075 mm. The sheet was then rolled. Before rolling, the roller gap X between the two rollers was adjusted to make X=0.060 mm. After rolling, a positive electrode sheet with a thickness of 0.058 mm was obtained. It contained 5.34 mg of active ingredient LFP.

[0028] Battery Assembly The above positive electrode is placed on the lower cover of a button-type lithium battery, and then 30 μl of lithium hexafluorophosphate (LiPF6) is dropped into a mixed solvent of EC / DEC=1:1 at a concentration of 1 mol / L to form an electrolyte, and then covered with Celgard 2325 (PP / PE / PP) diaphragm material. Finally, the lithium metal negative electrode material is placed in the upper cover and sealed to form a button-type lithium-ion secondary battery. The designed theoretical capacity of the NMC lithium-ion battery prepared by the present invention is 200 mAh / g, and the designed theoretical capacity of the LFP lithium-ion battery is 170 mAh / g.

[0029] Testing the viscosity properties of PVDF in different solvents Table 1 shows the respective viscosities of 4 wt% PVDF slurries prepared with different solvents measured by a rotary viscometer-viscosity tester (manufactured by Elcometer, UK, model Elcometer 2300).

[0030] Table 1 Viscosity of 4wt% polyvinylidene fluoride (PVDF) solution in different solvents Polyvinylidene fluoride (PVDF) Solvents Viscosity Polyvinylidene fluoride (PVDF) adhesive 1 Non-environmentally friendly solvent (NMP) 1336 Polyvinylidene fluoride (PVDF) adhesive 1 Environmentally friendly solvent (DEF) 1114 Polyvinylidene fluoride (PVDF) adhesive 2 Non-environmentally friendly solvent (NMP) 843 Polyvinylidene fluoride (PVDF) adhesive 2 Environmentally friendly solvent (DEF) 778 Test the contact angle of PVDF with different solvents on different foil surfaces The contact angles in Table 2 were measured by an optical water drop angle analyzer (manufactured by Creating Nano Technologies Inc., model OCA 40Micro) when PVDF slurries in different solvents were dropped on different foils.

[0031] Table 2 Contact angle of polyvinylidene fluoride (PVDF) solution on different current collectors Table 3 shows the results of battery cycle tests after electrodes prepared with a non-environmentally friendly solvent (NMP) and an environmentally friendly solvent (DEF) in some embodiments of the present disclosure are assembled into batteries respectively. Specifically, the positive and negative electrode materials of the battery are lithium (Li) and NMC (LxNiyMnzCo1-y-zO2 (0 < x, y, z < 1)) respectively. The aforementioned electrodes, separator, and electrolyte are assembled into a CR2032 button battery under an argon atmosphere, and the battery cycle test is carried out at room temperature with a BAT-750B type battery charger and discharger from UBIQ company.

[0032] Table 3 Cycling stability test of different solvents at a charge-discharge rate of 0.5 Coulomb (NMC811 / / Li) As Figure 1 shown, in an embodiment of the present invention, the capacitance of the electrode prepared with the non-environmentally friendly solvent (NMP) decays very fast. For example, only 52.1% of the original capacitance remains at the 100th cycle, while the environmentally friendly solvent (DEF) of the present disclosure still has 82.5% of the remaining capacitance at the 100th cycle. Therefore, it can be known that when the environmentally friendly solvent (DEF) of the present disclosure is applied in a battery, it can be seen that the low-toxicity environmentally friendly solvent has extremely low water absorption characteristics and does not produce free amines, which is not likely to cause the deterioration of the electrode sheet, so that the battery is more suitable for operation in the environment.

[0033] As Figure 2 and Figure 3As shown, in one embodiment of the present invention, a structure 100 of an improved electrode mainly includes: an electrode material 10, the electrode material 10 includes lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), lithium nickel cobalt aluminum oxide (NCA), silicon oxide carbon composite material (SiOx / C), silicon carbon composite material (Si / C), mesophase carbon microspheres (MCMB), lithium titanate (LTO), wherein the weight percentage of the electrode material 10 is 80-96%; a conductive material 20, the conductive material 20 includes conductive carbon black (Super-P), Ketjen black conductive agent (KB), conductive carbon tube (CNT), graphene (Gr aphene), wherein the weight percentage of the conductive material 20 is 2-10%; an adhesive 30, the adhesive 30 includes polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyimide (Polyimide), polyethylene oxide (PEO), wherein the weight percentage of the adhesive 30 is 2-10%; and a low-toxicity environmentally friendly solvent 40, the low-toxicity environmentally friendly solvent 40 includes dimethylformamide (DMF), diethylformamide (DEF), dimethylacetamide (DMAC), tetrahydrofuran (THF), the low-toxicity environmentally friendly solvent 40 is N, N-Diethyl formamide (DEF, N, N-diethylformamide), and the chemical formula of the low-toxicity environmentally friendly solvent 40 is (NR2R3OR1) wherein R1=H, Me(-CH3), R2=H, Me(-CH3), Et(-CH2CH3), R3=H, Me(-CH3), Et(-CH2CH3), wherein the weight percentage of the low-toxicity environmentally friendly solvent 40 in the positive electrode material is 20-70%, and in the negative electrode material is 100-150%; the boiling point of the low-toxicity environmentally friendly solvent 40 is ≦180°C at 1 atmosphere (a lower boiling point will reduce the baking temperature and shorten the baking time); the flash point of the low-toxicity environmentally friendly solvent 40 is ≧60°C, ≦80°C at 1 atmosphere (a flash point greater than 60°C is more favorable for the transportation of the solvent). less likely to have doubts); the thickness of the electrode material 10 is between 50μm and 200μm; the stirring temperature of the adhesive 30 solution is ≤60°C, and the process time is 0.5 to 6 hours; wherein the improved electrode structure 100 is baked at a temperature of 50-150 degrees, and the process time is 8 to 12 hours; wherein the improved electrode structure 100 can be cut into various shapes (for example: rectangle, rhombus, parallelogram, trapezoid, triangle, circle or irregular shape), and then wound or stacked to assemble into a battery; wherein when the improved electrode structure 100 is assembled into a battery, it can be used as a battery for a mobile device or a power battery for an electric vehicle or other types of batteries.

[0034] Through the above structure, the structure of the improved electrode of the present invention utilizes a low-toxic and environmentally friendly solvent and uses the solvent to prepare a lithium battery pole piece, thereby solving the technical problems of the prior art lithium battery pole piece slurry solvent (NMP) being expensive and easily causing harm to the environment and human body, and the solvent being easy to absorb water and easily causing battery instability due to free amines produced during manufacturing or recycling, which meets the needs of progress, practicality and users, and is sufficient to show its benefits.

[0035] The invention is characterized in that it replaces the use of solvents in the existing battery market and saves energy consumption required for the drying-recovery process in the battery manufacturing process; and is applied in the field of lithium-ion batteries.

[0036] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. An improved electrode structure, characterized in that: Mainly include: An electrode material, wherein the weight percentage of the electrode material is 80-96%; A conductive material, the weight percentage of the conductive material is 2-10%; an adhesive, wherein the weight percentage of the adhesive is 2-10%; and A low-toxic environmentally friendly solvent, wherein the weight percentage of the low-toxic environmentally friendly solvent in the positive electrode material is 20-70%, and in the negative electrode material is 100-150%; The improved electrode structure is baked at a temperature of 50-150 degrees and the process time is 8 to 12 hours.

2. The improved electrode structure as claimed in claim 1, characterized in that: The electrode material includes lithium nickel manganese cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt aluminum oxide, silicon oxide carbon composite material, silicon carbon composite material, mesophase carbon microspheres, and lithium titanate.

3. The improved electrode structure as claimed in claim 1, characterized in that: The conductive material comprises conductive carbon black, Ketjen black conductive agent, conductive carbon tube and graphene.

4. The improved electrode structure as claimed in claim 1, characterized in that: The adhesive comprises polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyimide and polyethylene oxide.

5. The improved electrode structure as claimed in claim 1, characterized in that: The low-toxic environmentally friendly solvent includes dimethylformamide, diethylformamide, dimethylacetamide and tetrahydrofuran.

6. The improved electrode structure as claimed in claim 1, characterized in that: The chemical formula of the low-toxic and environmentally friendly solvent is (NR2R3OR1) where R1=H,Me(-CH3), R2=H,Me(-CH3),Et(-CH2CH3), R3=H,Me(-CH3),Et(-CH2CH3).

7. The improved electrode structure as claimed in claim 1, characterized in that: The boiling point of this low-toxic, environmentally friendly solvent is ≤180°C at 1 atmosphere.

8. The improved electrode structure as claimed in claim 1, characterized in that: The flash point of the low-toxic and environmentally friendly solvent is ≧60°C and ≦80°C at 1 atmosphere.

9. The improved electrode structure as claimed in claim 1, characterized in that: The thickness of the electrode material is between 50 μm and 200 μm.

10. The improved electrode structure as claimed in claim 1, characterized in that: The adhesive solution is stirred at a temperature of ≤60° C. and the process time is 0.5 to 6 hours.